COVID-19 as a Double-edged Sword: The Perfect Opportunity for GrabFood to Optimize Its Performance - Daisy Mui Hung Kee; Maryam Al-anesi; Swetha Chandran; Haritra Elanggovan; Buventhran Nagendran; Sharvin Mariappan (AIBPM Publisher, 2021)
This research underscores the critical role COVID-19 plays in potentially sharpening the resilience of GrabFood company to its greatest degree. As a temporary double-edged sword, it could optimize the performance and customer satisfaction of GrabFood in the long run. Our findings revolve around anecdotal evidence of issues that, if altered, could help its loyal customers and gain new ones in such a sensitive era. To address the challenges that restrict GrabFood from transforming into a more flexible online platform, an online survey was carried out with both GrabFood customers and employees. The study's findings indicated that GrabFood is gaining its popularity during the outbreak of the COVID-19 crisis. The post-pandemic arising obstacles will be further stressed, and solutions will be suggested based on secondary data collected from observations of other high-performance level companies like Foodpanda.